Association analysis of single nucleotide polymorphisms in the sheep FecB gene with reproductive and body size performance - L. Kong; S. Li; Y. Pan; J. Li; S. Li; Y. Liu; S. Hou; Q. Liu; Y. Qiao; Y. Sun; Z. Wang (Archives Animal Breeding, 2024)
The FecB gene is one of those responsible for regulating reproductive traits in sheep. This experiment was designed to explore the impact of SNPs (single nucleotide polymorphisms) within the FecB gene on both the reproductive and body size performance of sheep. In this experiment, two SNP sites were identified as C413217T and A431965G. Through analysis of genetic diversity and correlations, we aimed to identify combinations of genotypes and haplotypes that influence reproductive performance and body size performance. The most prominent genotypes associated with lambing performance were identified as AA and CT, with the dominant haplotype combination being AACT. For body size performance, the dominant genotypes were AA and CC, while the dominant haplotype combination was AACC. These advantageous genotypes and haplotype combinations are conducive to promoting the selection and improvement of sheep breeds, advancing the progress of sheep genetic breeding, and providing theoretical support for the breeding of higher-fertility sheep.